CIPLUKAN’S ANTI-INFLAMMATORY EFFECTS: MECHANISMS UNCOVERED - Prasetyo, Yacobus Christian; Purwanti, Noerlina (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Background: Ciplukan (Physalis angulata Linn) is a native American plant widely distributed in tropical regions including Indonesia. This herb has been used as a traditional ingredient to treat inflammation as well as other diseases. Ciplukan’s anti-inflammatory effects are thought to be triggered by the active compounds in the various parts of the herb. Objective: This review aims to describe the herb’s anti-inflammatory effects and its mechanisms. Methods: PubMed and Google Scholar databases were searched for articles using Boolean operations with keywords related to Physalis angulata and inflammatory components. We included literature in English and Indonesian without limiting the publication time range. Results: Ciplukan has an anti-inflammatory effect by regulating inflammatory mediators, inhibiting immune signaling pathways, and the genes associated with the immune system.